Serum Ferritin Levels for the Prediction of Mortality among COVID-19 Patients in an Indonesia’s National Referral Hospital - Chicamy, Yoshie Anto; Safitri, Annisa; Nindrea, Ricvan Dana (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Early identification of clinical outcomes is necessary for risk classification in COVID-19 patients. This study help in evaluating the progression of the disease and the patient’s therapy. AIM: This study aims to determine serum ferritin levels for the prediction of mortality among COVID-19 patients in an Indonesia’s National Referral Hospital. METHODS: A retrospective cohort study was conducted on 142 confirmed positive COVID-19 patients between March 2020 until March 2021 at Dr. M. Djamil General Hospital as a National Referral Hospital in Indonesia. Data obtained from medical record documents and examination of ferritin levels was carried out at the beginning of treatment. The Chi-square test and survival analysis with the log-rank test and Kaplan–Meier methods were used to analyze the data. The SPSS version 15 was used to analyze the data. RESULTS: The serum ferritin cutoff point for COVID-19 patients that can be used to predict poor outcomes was >651.02 ng/mL with sensitivity 79.3%, specificity 80.5%, and accuracy 85.0%. Age, comorbid diabetes mellitus, number of comorbidities, symptoms of trouble breathing, oxygen saturation, severity, and mortality outcome were all associated to ferritin levels >651.02 ng/mL. The Kaplan–Meier curve showed that ferritin levels >651.02 ng/mL were associated for risk of poor outcome COVID-19 patients (HR = 8.84, [95% CI 3.59–21.73]). CONCLUSION: The ferritin cutoff point for predicting poor prognosis in COVID-19 patients was 651.02 ng/mL. However, ferritin serum levels cannot be used as a single predictor in determining the poor outcome of COVID-19.